Application Research of Individualized Conditional Reprogramming System to Guide Treatment of Gastric Cancer - Zhao, Weizhu; Liu, Kai; Sun, Zhikun; Wang, Longgang; Liu, Bing; Liu, Luguang; Qu, Xianlin; Cao, Zhixiang; Sun, Jujie; Chai, Jie (Frontiers in Oncology, 2021)
Background: Gastric cancer （GC）is one of the most common causes of malignant tumors in the world. Due to the high heterogeneity of GC and lack of specificity of available chemotherapy regimens, these tumors are prone to resistance, recurrence and metastasis. Here, we formulated an individualized chemotherapy regimen for GC using a modified individual conditional reprogramming(i-CR) system. We established a primary tumor cell bank of GC cells and completed drug screening in order to realize individualized and accurate GC treatment. Methods: we collected specimens from 93 surgical or gastroscopy GC cases and established a primary tumor cell bank using the i-CR system and PDX models. We also completed in vitro culture and drug sensitivity screening of the GC cells using the i-CR system. Whole-exome sequencing (WES) of the i-CR cells was performed using P0 and P5. We then chose targeted chemotherapy drugs based on the i-CR system results. Results：Of the 72 cases were collected from surgical specimens, 26 cases were successfully cultured with i-CR system, and of the 21 cases collected from gastroscopy specimens, seven were successfully cultured. Among these, 20 cases of the PDX model were established. SRC ±G3 had the highest culture success rate. The i-CR cells of P0 and P5 appeared to be highly conserved. According to drug sensitivity screening, we examined the predictive value of GC patients’ responses to chemotherapeutic agents, especially in neoadjuvant patients. Conclusion: The i-CR system does not only represent the growth characteristics of tumors in vivo, but also provides support for clinical drug use. Drug susceptibility results were relatively consistent with clinical efficacy.